Rekonstruksi Metode Pendidikan Islam dan Pendidikan Umum untuk Pendidikan Holistik di Era Disrupsi - Ida Zahara Adibah; Diyah Nuraini Mahmudah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
ABSTRACT This study aims to analyze the integration of general and Islamic education methods as a solution to the dichotomy of knowledge in modern educational systems. Using a qualitative approach with a library research method, this paper explores how active learning techniques in general education can be synchronized with spiritual values and character building in Islamic education. The results indicate that merging Student-Centered Learning strategies with the concepts of Ta’dib and Tazkiyatun Nafs can create a holistic pedagogical architecture. This integration focuses not only on developing intellectual intelligence and technical skills but also emphasizes the internalization of adab (etiquette) and the moral integrity of students in the era of disruption. Furthermore, the synchronization of these two methods provides a strong epistemological foundation for developing a curriculum that is relevant to global needs without sidelining religious identity. In conclusion, the synergy between empirical secular methodology and revelation-based Islamic methodology is a necessity for producing a generation that is professionally competitive and spiritually stable. This study recommends the implementation of standardized integrative curriculum frameworks across various educational levels.